eHealth Internet of Things on Low Power Wide Area Network of Hospital - Manatarinat, Wiraphon; Tantatsanawong, Panjai; Poomrittigul, Suvit; Udomsiri, Sakol (My University, 2023)
Nowadays, the number of older adults is increasing due to medical advancements and attention to the health of the elderly. Effective healthcare and safety are essential. Therefore, the researcher has an idea to develop a system that can support the care of patients and the elderly safely by detecting falls. However, there are limitations in the contact with the public health system and other technical issues such as high power consumption, cost, and reliability. In this article, we would like to introduce a fictional wearable fall detection system. Algorithms based on threshold are specifically integrated with the Internet of Things (IoT) and a Low-Power Wide Area Network (LPWAN), with nodes monitoring and parsing the data. The server part consists of an application server and a UDP server. The application server is responsible for accessing the data. At the same time, the UDP server is responsible for receiving data and monitoring abnormal data packets sent by the Narrowband Internet of Things (NB-IoT) to develop an efficient and secure data transmission mechanism. For healthcare professionals, eHealth is designed from the server side, which comprises a server application and a client-server architecture. The eHealth system is a digital technology tool and ICT service that connects healthcare providers and citizens to access health services effectively, comprehensively, equitably, and safely for elderly patients and healthcare providers for algorithm validation. We recruit volunteers for events. Daily life and falls the experimental results showed that our presented algorithm could achieve accuracy, indicating the efficiency of our system.
Keywords: eHealth System; Fall Detection; LoRaWAN; NB-Internet of Things